GENETIC DIVERSITY ANALYSIS OF ZEA MAYS L. ACCESSIONS BASED ON MICROSATELLITE MARKERS - Yermagambetova, M.M.; Ibraimov, A.M.; Ortaev, A.K.; Makhmadzhanov, S.P.; Turuspekov, Y.K. (Eurasian Journal of Applied Biotechnology, 2025)
This study aimed to evaluate the genetic diversity of 21 maize (Zea mays L.) accessions cultivated in Kazakhstan using 21 SSR markers. The selected markers revealed substantial polymorphism, with polymorphic information content (PIC) values ranging from 0.557 to 0.962, indicating high marker informativeness. Genetic diversity indices such as the number of alleles (Na), effective number of alleles (Ne), Shannon’s information index (I), and Nei’s gene diversity index (uh) varied significantly among accessions, with the Kazakh accession ZM001 showing the highest diversity. Analysis of Molecular Variance (AMOVA) revealed that 66% of the total genetic variation was attributable to differences among accessions, confirming strong population differentiation (Fst = 0.611) among maize accessions. Cluster analysis, Principal Coordinate Analysis (PCoA), and STRUCTURE analysis consistently grouped accessions according to their geographic origin, distinguishing local, Chinese, and European accessions. These results highlight the effectiveness of SSR markers in revealing genetic structure and demonstrate the existence of untapped allelic variation in the maize germplasm of Kazakhstan.